A Critical Note on the Forecast Error Variance Decomposition - Atilim Seymen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
The paper questions the reasonability of using forecast error variance decompositions for assessing the role of different structural shocks in business cycle fluctuations. It is shown that the forecast error variance decomposition is related to a dubious definition of the business cycle. A historical variance decomposition approach is proposed to overcome the problems related to the forecast error variance decomposition.
Keywords: C32; E32; 330; Business Cycles; Structural Vector Autoregression Models; Forecast Error Variance Decomposition; Historical Variance Decomposition; Konjunkturprognose; Prognoseverfahren; Statistischer Fehler; Varianzanalyse; Dekompositionsverfahren; VAR-Modell; Theorie; HVD